The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/prac.19883300516
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthesis of 1,3 Thiazetidine‐2‐one and 1,3‐Oxazine‐2‐one Derivatives

Abstract: In the reactions of acetylthioacetanilides (1a–c) and diacetylthioacetanilides (3a–f) with phosgene 1,3‐thiazetidine‐2‐one (2a–c) and 1,3‐oxazine‐2‐one (5a–f) were obtained respectively. The structures of new compounds were elucidated by elemental analyses, i.r., 1H‐n.m.r., m.s., for 1d–f by 19F‐n.m.r. and for 2a and 5a by 13C‐n.m.r. spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…On the basis of analytical and spectral data we found that 8 underwent regiospecific S,N alkylation and this process was accompanied by hydrolysis of enamines to keto derivatives (Scheme 3). Some of the compounds obtained were found to be identical with those reported recently [8] and obtained by alkylation of benzoylthioacetanilide. Considering the result of the alkylation of enamines 8, we rulled out their preliminary hydrolysis to keto compounds and their further alkylation on the basis of following experimental data.…”
Section: Methodssupporting
confidence: 80%
“…On the basis of analytical and spectral data we found that 8 underwent regiospecific S,N alkylation and this process was accompanied by hydrolysis of enamines to keto derivatives (Scheme 3). Some of the compounds obtained were found to be identical with those reported recently [8] and obtained by alkylation of benzoylthioacetanilide. Considering the result of the alkylation of enamines 8, we rulled out their preliminary hydrolysis to keto compounds and their further alkylation on the basis of following experimental data.…”
Section: Methodssupporting
confidence: 80%
“…Compounds 1a-f and 2a-f were prepared according to [11] and [10], respectively. X-Ray investigation.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous investigation [10], with such double acylating reagent as phosgene, 1,3-oxazine derivatives 2 were isolated as the result of O-and N-acylation of N-aryldiacetylthioacetamides 1. However, a different course of reaction was observed when oxalyl chloride was used.…”
mentioning
confidence: 99%
“…Acid treatment results in a cyclic lactone, and in rearrangement of thiopyrane derivatives to a thermodynamically more stable pyridine ring, due to which a derivative of furo [3.4- Compounds 2 a-d mere obtained according to [2] based on the Knoevenagel reaction of 2-(aroylmethylidene)-3-aryl thiazolidine-4.5-dione 1 a-d with malononitrile in ethanol a t 60°C.…”
mentioning
confidence: 99%